2005
DOI: 10.1080/09637480500410085
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of glycerol as carbon source on the growth, pigment and lipid production inSpirulina platensis

Abstract: The ability of the cyanobacterium Spirulina platensis to utilize glycerol as the carbon source was investigated. In this work, we report on some physiological parameters that characterize the adaptive response of Spirulina platensis for the utilization of glycerol as the carbon source. A marked decrease was observed in the pigments Chlorophyll a (Chl a) and phycocyanin content of Spirulina platensis grown on glycerol medium when compared to the control. The lipid content in the glycerol-grown groups was compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
1
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 17 publications
4
19
1
1
Order By: Relevance
“…used in the present study achieved higher biomass concentrations compared to previous studies concerning Arthrospira sp. Narayan et al, 2005;Radmann et al, 2007). This species had higher growth rate (µ) than in previous studies for Arthrospira sp.…”
Section: Discussioncontrasting
confidence: 39%
“…used in the present study achieved higher biomass concentrations compared to previous studies concerning Arthrospira sp. Narayan et al, 2005;Radmann et al, 2007). This species had higher growth rate (µ) than in previous studies for Arthrospira sp.…”
Section: Discussioncontrasting
confidence: 39%
“…For example, lipids and pigments have been produced from glycerol by cyanobacterium Spirulina platensis (Narayan et al 2005). Docosahexaenoic acid (DHA) and other lipids were generated from a marine microalga, Schizochytrium limacinum SR21 grown on glycerol (Pyle et al 2008).…”
Section: Dry Weight (G/l)mentioning
confidence: 99%
“…It was reported that biomass productivity in C. protothecoides was increased when glycerol was used as carbon source [38]. When glycerol was used for cyanobacterium Spirulina platensis, lipids and pigments production was increased [24]. Similarly, when marine microalga Schizochytrium limacinum SR21 was grown on glycerol, docosahexaenoic acid (DHA) and other lipids were produced [27].…”
Section: Effect Of Glycerol On Mixotrophic Cell Growth and Lipid Contentmentioning
confidence: 99%